Synthesis and Characterization of pH Tolerant and Mucoadhesive (Thiol–Polyethylene Glycol) Chitosan Graft Polymer for Drug Delivery. Issue 2 (30th December 2013) - Hauptstein, Sabine; Bonengel, Sonja; Griessinger, Julia; Bernkop‐Schnürch, Andreas
<x xml:space="preserve">Abstract</x> The objective of this study was to generate a water‐soluble thiolated chitosan to enable the permeation‐enhancing effect of chitosan at pH of at least 5.5 without losing the advantages of improved mucoadhesive properties. Therefore, the thiol‐bearing polyoxyethylene ligand {O‐(3‐carboxylpropyl)‐O′‐[2‐[3‐mercaptopropionylamino)ethyl]‐polyethyleneglycol} was conjugated via amide bond formation to the amino group of chitosan. Resulting novel chitosan derivative (Chito–PEG–SH) exhibited 250 μmol free thiol groups per gram polymer. By the attachment of the thiol‐bearing PEG ligand, an improvement of permeation‐enhancing effect on rat intestine (2.7‐fold improvement) as well as on a Caco‐2 monolayer model (1.9‐fold improvement) could be found. Cytotoxicity studies on Caco‐2 cells revealed no change in biocompatibility. Mucoadhesion was improved 3.1‐fold by the formation of disulfide bonds with mucus glycoproteins. The mucoadhesive effect of Chito–PEG–SH turned out to be similar to thiolated chitosan and more pronounced than mucoadhesive properties of unmodified chitosan. The graft polymer is soluble in water and aqueous solutions over a broad pH range. In aqueous media, the novel polymer does not precipitate at pH of 8.6 or less. According to these results, Chito–PEG–SH might show potential as auxiliary agent in oral drug delivery where its solubility even up to pH 8 is likely beneficial. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 103:594–601, 2014